An evaluation of the outcomes of the calibration and validation of the RUMINANT Model for Colombia - Camacho, Kemly (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
This report is an evaluation of the outcomes of the calibration and validation of the RUMINANT Model for Colombia.